O processo de identificação dos membros de tribos urbanas: o caso do grupo de motociclismo da Harley-Davidson - Duarte, Priscila da Silva (2019)
Based on the observation that we live in a society of groups that seek different and multiple affiliations, this thesis, based mainly on the studies of Sigmund and Anna Freud and Michel Maffesoli, had as general objective to investigate how the process of identification between members of urban tribes. And, its specific objectives were to identify the shared meanings and perceived difference of these members in relation to themselves, others and the group image; to point out the symbolic, material, ritual aspects and how the power relations that mark their identities are organized; and examine how the discourses enunciated in this urban tribe are incorporated into the daily reality of its members. The methodology used was qualitative, developed through semi-structured interviews, conducted between August and October of 2018, in the southern states, with 26 owners of HarleyDavidson motorcycles affiliated with the brand's official motorcycle group, the 88Harley-Davidson Owners Group, whose testimonies were submitted to content analysis. We conclude that the process of identification in the urban tribes occurs through the transformation of people through group illusion. Created through the experiences of group life, this illusion influences feelings as well as shared meanings of caring, friendship and trust, leading members to feel like special people, protects the group against future dismemberments and external groups, alleviates conflicts arising from different power relations, and involves members and their families in the same group fantasy, including in everyday life.